Temperature Dependent Phonon Shifts in Single-Layer WS2 - Thripuranthaka, M.; Late, Dattatray J. (Acs Applied Materials & Interfaces, 2014)
Atomically thin two-dimensional tungsten disulfide (WS2) sheets have attracted much attention due to their potential for future nanoelectronic device applications. We report first experimental investigation on temperature dependent Raman spectra of single-layer WS2 prepared using micromechanical exfoliation. Our temperature dependent Raman spectroscopy results shows that the E-2g(1) and A(1g) modes of single-layer WS2 soften as temperature increases from 77 to 623 K. The calculated temperature coefficients of the frequencies of 2LA(M), E-2g(1), A(1g), and A(1g)(M) + LA(M) modes of single-layer WS2 were observed to be -0.008, -0.006, -0.006, and -0.01 cm(-1) K-1, respectively. The results were explained in terms of a double resonance process which is active in atomically thin nanosheet. This process can also be largely applicable in other emerging single-layer materials.
Keywords: layered materials; phonon vibrations; Raman spectroscopy; thermal effect; WS2

Hydrothermal synthesis of WS2/RGO sheet and their application in UV photodetector - Shelke, Nitin T.; Karche, B. R. (Journal of Alloys and Compounds, 2015)
Two-dimensional (2D) semiconductor nanomaterials hold great promises for future electronics and optics. In this paper, we report UV photocurrent response of 2D hybrid materials consisting of layered WS2 nanosheets and reduced graphene oxide prepared by using one step hydrothermal method. Few-layer WS2 and WS2/RGO nanosheets are characterized by Raman spectroscopy and HRTEM. The electric and optoelectronic properties of WS2 and WS2/RGO based UV photodetector shows a fast response of 48s and 85s and high photosensitivity (80 mu AW(-1) and 3.21 mAW(-1)) indicating that the two-dimensional composite nanostructure WS2/RGO is an important material for high performance photodetectors. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: nanosheets; UV photodetector; WS2; WS2/RGO

WS2 nanoparticle-decorated, vertically aligned SnS2-based high-performance heterostructures for ambient-stable ultrafast photodetection - Das, Chayan; Kumar, Suresh; Sharma, Anjali; Kumar, Mahesh; Rath, Arup K.; Sahu, Satyajit (ACS Applied Nano Materials, 2025)
The development of visible-light photodetectors with high responsivity, rapid response, and long-term ambient stability remains a critical challenge in optoelectronics. Here, we report a high-performance photodetector based on a vertically aligned SnS2 film interfaced with WS2 nanoparticles, forming a p-n heterojunction. This device is fabricated using a scalable two-step method-chemical vapor deposition (CVD) for SnS2 growth and solution-based drop-casting for WS2 deposition-enabling precise control over the heterointerface, but trap states are inevitable due to the use of thermal CVD and the drop-casting method. The resulting photodetector exhibits remarkable optoelectronic characteristics, including a responsivity of 0.76 A/W, a detectivity of 7.56 x 10(11) Jones, a photo-to-dark current ratio of 119, and a fast rise time of 0.297 ms under visible illumination. These performance metrics are directly attributed to the optimized heterointerface, where the built-in electric field at the nanoscale WS2/SnS2 junctions promotes efficient charge separation and minimizes recombination losses. Notably, the device retains over 95% of its initial performance even after 1 week of ambient exposure, highlighting its superior environmental robustness. This work introduces an interface-engineering strategy that leverages the unique electronic properties of earth-abundant, nontoxic two-dimensional materials, offering a viable pathway for scalable, high-speed, and stable photodetectors suitable for next-generation optoelectronic systems.
Keywords: 2D; CVD; heterojunction; photodetector; SnS2; WS2